Considering the autogenic processes of the ecosystem to analyze the sensitivity of peatland carbon accumulation to temperature and hydroclimate change - Liu, Hanxiang; Han, Dongxue; Wang, Guoping (Catena (Giessen), 2024)
Peatland carbon accumulation plays a vital role in the global carbon pool and climate change dynamics. However, understanding how peatland carbon accumulation responds to climate change is challenging due to the influence of autogenic processes on carbon dynamics. In this study, we investigate the temporal variations of the Non-autogenic Carbon Accumulation Rate (NCAR) over approximately 1500 years in a peatland located in the Amur River Basin. To remove the effects of autogenic processes, we use conceptual models of peat development and employ plant macrofossils to identify vegetation changes, particularly the fen-bog phase transition. We apply different exponential decay models to capture autogenic processes in the fen and bog phases of the peatland. Subsequently, we analyze the sensitivity of peatland carbon accumulation to temperature and hydroclimate changes in the fen and bog phases, respectively. Our findings show that in the fen phase, higher temperature increases plant litter decomposition more than the plant net primary productivity (NPP) when water content is high, leading to lower NCAR. However, as temperature rises and water content is no longer a limiting factor, plant NPP surpasses plant litter decomposition, resulting in high NCAR. In the bog phase, we find no significant correlation between NCAR and precipitation but observe a positive relationship between NCAR and temperature. These results enhance our understanding of the connections between temperature, moisture, and peatland carbon accumulation by considering the influence of autogenic processes.